Foreign trade in Prime Bank Limited, international trade in Bangladesh & worldwide scenario - Polash, Mahmudur Rahman (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.